Risk factors and human coronaviruses associated with upper respiratory tract infections in three rural areas of Ghana - Owusu, Michael (2017)
A thesis submitted to the Department of Clinical Microbiology, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the degree of Doctor Of Philosophy, School of Medical Sciences, College of Health Sciences.